THE CURRENT STATE OF THE PROBLEM OF LARYNGEAL PAPILLOMATOSIS IN CHILDREN (LITERATURE REVIEW) - Mahamadaminova Sh.A.; Makhmudova Kh. J.; Akromova M. B (Web of Journals Publishing, 2024)
Despite the successes achieved in recent years in solving the problems of respiratory papillomatosis, the most important issues in terms of diagnosis, surgical and conservative treatment (anti-relapse), as well as forecasting the course and outcome of the disease remain unresolved. Therefore, the problem of treating respiratory papillomatosis is one of the most important and relevant in otorhinolaryngology. Its significance is due to the fact that, affecting the larynx, papillomatous growths narrow its lumen, which leads to impaired vocal and respiratory function. Chronic respiratory hypoxemia, which develops in this regard, is the cause of violations of the physical, psychomotor and emotional development of the child.
Keywords: laryngeal papillomatosis, larynx, virus.